PENDAMPINGAN MTQ INTERNASIONAL SEBAGAI SARANA PENINGKATAN KOMPETENSI TILAWAH DAN TAHFIZH DI TINGKAT GLOBAL - Sufyan Muttaqin; Mukhammad; Muhith; Rasyid; Armizi (LPPM STAI Muhammadiyah Probolinggo, 2024)
The International Musabaqah Tilawatil Qur’an (MTQ) is a strategic event to showcase the best tilawah (Qur’anic recitation) and tahfizh (Qur’anic memorization) skills at the global level, while also serving as a means of Qur’anic cultural diplomacy. However, the achievements of Indonesian participants at the international level still face challenges, particularly in aspects such as the accuracy of tajweed, fashahah (articulation clarity), mastery of melody, fluency of memorization, and mental readiness for performance. This community service research aims to describe the process and outcomes of the International MTQ mentoring program as an effort to enhance tilawah and tahfizh competencies. The method employed is a participatory approach involving pre-assessment of initial competencies, intensive training (talaqqi, sima’an, peer feedback), competition simulations, as well as mental and stage management coaching. The target group consists of prospective International MTQ participants who have passed the national selection stage. The mentoring results show a significant improvement in tilawah scores (average increase of 18%) and tahfizh scores (average increase of 15%) based on International MTQ assessment standards. In addition, participants demonstrated increased self-confidence, voice control, and memorization accuracy during the simulation stage. These findings affirm that structured mentoring, based on a holistic Qur’anic training method, can serve as an effective strategy for preparing globally competitive participants while strengthening Indonesia’s image as a global center for Qur’anic development.